An Autologous Protein-Based Topical Ointment for Hard-to-Heal Skin Wounds: A Multiple Case Series. Issue 4 (July 2021) - Muñoz, Victoria; Pino, Ander; Martinez, Carmen; Echevarria, Begoña; Lacramioara, Varlan; Anitua, Eduardo
Abstract : BACKGROUND: There is increasing evidence regarding the wound healing potential of platelet-derived autologous by-products. We provide preliminary data regarding the use of a new plasma rich in growth factors–derived autologous topical ointment for the management of hard-to-heal wounds. CASES: Four patients suffering from difficult-to-heal wounds were treated with the autologous ointment. Within 2 to 8 weeks, all wounds healed completely with no signs of infection or functional impairment of the affected limbs. No adverse events were reported. CONCLUSION: Randomized and controlled trials are needed to determine the clinical efficacy of the autologous ointment. Nevertheless, results from this multiple case series indicate that this approach may be useful for accelerating the re-epithelization of difficult-to-heal wounds.